2006
DOI: 10.1007/s00239-005-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Population Genetics of the α-Esterase5 Gene Locus in Original and Colonized Populations of Drosophila buzzatii and Its Sibling Drosophila koepferae

Abstract: Several studies have suggested that esterase-2 (EST-2) may be the target of natural selection in the cactophilic fly Drosophila buzzatii. In this work, we analyzed nucleotide variation in a fragment of alpha-esterase5 (alphaE5), the gene encoding EST-2, in original (Argentinian) and colonized (Australian) populations of D. buzzatii and in its sibling D. koepferae. Estimates of nucleotide heterozygosity in D. buzzatii were similar in Australia and Argentina, although we detected a loss of singletons in colonize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 66 publications
0
16
0
1
Order By: Relevance
“…Demographic history of D. buzzatii in Australia Previous comparisons of Australian populations with original ones in Argentina support a bottleneck at the time of introduction, with the former showing reduced variability for allozyme (Barker et al, 1985), mitochondrial DNA (Halliburton and Barker, 1993), microsatellite (Frydenberg et al, 2002; Table 1) and other molecular (Piccinali et al, 2007) polymorphisms. Distributions of the overall Australian and Argentinian allele frequencies at 15 microsatellite loci (Figure 4) show not only the reduced variability of the former, but also dramatic shifts at many of the loci-clear signals of a founding bottleneck.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic history of D. buzzatii in Australia Previous comparisons of Australian populations with original ones in Argentina support a bottleneck at the time of introduction, with the former showing reduced variability for allozyme (Barker et al, 1985), mitochondrial DNA (Halliburton and Barker, 1993), microsatellite (Frydenberg et al, 2002; Table 1) and other molecular (Piccinali et al, 2007) polymorphisms. Distributions of the overall Australian and Argentinian allele frequencies at 15 microsatellite loci (Figure 4) show not only the reduced variability of the former, but also dramatic shifts at many of the loci-clear signals of a founding bottleneck.…”
Section: Discussionmentioning
confidence: 99%
“…This is in clear contrast with the ∼1 Myr and ∼0.5 Myr old inversions 2j and 2q 7 where 17 and 14 fixed nucleotide substitutions were observed, respectively [38], [60]. The monomorphism of the α-esterase5 gene in 2jz 3 chromosomes is also consistent with a recent origin of inversion 2z 3 [98]. In spite of being a very young inversion, 2z 3 exhibits a widespread distribution in natural populations (see Introduction), suggesting that it must have a considerable selective value.…”
Section: Discussionmentioning
confidence: 78%
“…There is a great difference between the percentages of non-synonymous replacements in D. buzzatii hsp23, hsp26 and phsp26 and all of them are lower than the percentages for D. buzzatii Xdh, α-E5 and αE5 (Table 1; Gómez and Hasson 2003;Piccinali et al 2004Piccinali et al , 2007. But analyses of the DNA variation in different genes within and between Drosophila species have shown that there is great variation in the percentage of non-synonymous replacements both between genes within species and between species (Moriyama and Powell 1996;Andolfatto 2001;Piccinali et al 2004).…”
Section: Intra-specific Sequence Variation and Its Ecological Associamentioning
confidence: 93%
“…The levels of nucleotide heterozygosity of hsp23, hsp26 and phsp26 were estimated by means of π and θ and compared to π and θ values of other D. buzzatii genes (Table 1; Gómez and Hasson 2003;Piccinali et al 2004Piccinali et al , 2007. The total π and θ values for hsp23 and hsp26 were lower than that for Xdh, α-E5 and Est-A, whereas for phsp26 it was in between the values for the other genes.…”
Section: Identification Of Putative Response Element By Comparative Smentioning
confidence: 98%